Synthetic Fertilizer Application Coupled with Bioslurry Optimizes Potato (Solanum tuberosum) Growth and Yield - Shao, Zeqiang; Mwakidoshi, Emmanuel R.; Muindi, Esther M.; Soratto, Rogério P. [UNESP]; Ranjan, Shivani; Padhan, Smruti Ranjan; Wamukota, Andrew W.; Sow, Sumit; Wasonga, Daniel O.; Nasar, Jamal; Seleiman, Mahmoud F.; Gitari, Harun I. (MDPI, 2023)
Biogas bioslurry, which is normally a bio-digestion product from livestock refuse, can be utilized as an inorganic fertilizer, thus boosting not only soil fertility but also crop growth and yield. Its use can mitigate climate change by reducing methane gas emissions, which are associated with the direct application of fresh animal manure. The current study was carried out on farmer’s fields based at Wusi-Kishamba and Werugha wards in Taita Taveta County, Kenya, and it aimed at investigating the effect of bioslurry coupled with synthetic fertilizer on potato (Solanum tuberosum L.) growth and yield. There were four treatments: sole bioslurry, sole fertilizer (DAP), bioslurry + DAP, and control, which were replicated five times in a randomized, complete block-designed layout. Data were collected on plant growth (plant height and leaf length) and yield (marketable and unmarketable tubers and the number of tubers plant−1). The results indicated a general increase in plant height from week one to week seven, where peak values were noted with sole slurry, sole fertilizer, and bioslurry + DAP treatments, which recorded 9, 18, and 43% taller plants, respectively, relative to control. Further, the combined application of bioslurry and DAP fertilizer significantly (p ≤ 0.05) improved potato growth and yield. For instance, there was a higher (23.3 t ha−1) yield in bioslurry + DAP treatment compared to the respective least record of 14.2 t ha−1 in control. Therefore, the study recommends a synergistic application of synthetic fertilizer (DAP) and bioslurry to potato crops for optimal crop growth and production.
Keywords: biogas; inorganic fertilizer; organic fertilizer; soil fertility; sustainable crop production